Strand breaks without DNA rearrangement in V (D)J recombination. - Hendrickson, E A (1991)
Somatic gene rearrangement of immunoglobulin and T-cell receptor genes [V(D)J recombination] is mediated by pairs of specific DNA sequence motifs termed signal sequences. In experiments described here, retroviral vectors containing V(D)J rearrangement cassettes in which the signal sequences had been altered were introduced into wild-type and scid (severe combined immune deficiency) pre-B cells and used to define intermediates in the V(D)J recombination pathway. The scid mutation has previously been shown to deleteriously affect the V(D)J recombination process. Cassettes containing a point mutation in one of the two signal sequences inhibited rearrangement in wild-type cells. In contrast, scid cells continued to rearrange these cassettes with the characteristic scid deletional phenotype. Using these mutated templates, we identified junctional modifications at the wild-type signal sequences that had arisen from strand breaks which were not associated with overall V(D)J rearrangements. Neither cell type was able to rearrange constructs which contained only a single, nonmutated, signal sequence. In addition, scid and wild-type cell lines harboring cassettes with mutations in both signal sequences did not undergo rearrangement, suggesting that at least one functional signal sequence was required for all types of V(D)J recombination events. Analysis of these signal sequence mutations has provided insights into intermediates in the V(D)J rearrangement pathway in wild-type and scid pre-B cells.